The relationship between Black and gay community involvement and HIV-related risk behaviors among Black men who have sex with men. Issue 1 (2nd January 2018) - Hotton, Anna L.; Keene, Lance; Corbin, Dennis E.; Schneider, John; Voisin, Dexter R.
ABSTRACT: Black gay men must navigate identities and stigmas related to being gay and Black, and report higher HIV incidence relative to their White male counterparts although they report lower rates of drug use and risky sexual behaviors. This study examined whether closeness to the gay or Black community correlated with HIV-related risk and protective behaviors. Data were drawn from uConnect, a population-based cohort study of young Black men who have sex with men (YBMSM) on Chicago's South Side. The sample consists of 618 Black MSM ranging in age from 16 to 29. Cross-sectional measures for this study include Black and gay community closeness, drug use, sexual risk behaviors, HIV testing, and health promotion behaviors. Closeness with the gay community was associated with greater pre-exposure prophylaxis (PrEP) knowledge as well as participating in health promotion programs along with higher rates of transactional sex and having sex under the influence of substances, and increased odds of self-reported HIV seropositivity. Involvement in the Black community was associated with lower odds of reporting being HIV positive. Findings suggest that programs and initiatives are needed to help promote the positive aspects of the Black and gay communities, while minimizing the negative correlates of such involvements.